Respostas fisiológicas de gramíneas de cobertura de solo submetidas ao excesso de manganês e cobre e sua interação com videira - Thiesen, Leonardo Antonio (2022)
Manganese (Mn) and copper (Cu) are micronutrients that have been showing a relevant increase in their concentration in the soil in vineyard areas, where there is constant application of fungicides containing these elements. The study objective to evaluate physiological and biochemical responses of ground cover grasses under conditions of excess Mn and under combination with excess Cu, as well as their potential to attenuate the toxicity of these metals in vine plants. For this, three experiments were carried out in a greenhouse. Experiment 1 was carried out in a nutrient solution with excess Mn (2 [control], 300, 600 and 900 μM) in different species of ground cover grasses (Paspalum notatum, Paspalum plicatulum, Avena strigosa and Lolium multiflorum). Experiment 2 was carried out in nutrient solution with the same species and with interaction of excess Cu and Mn. For this, combinations containing low and high concentrations of Mn (300 and 900 μM), and Cu (0.5 and 40 μM), respectively, were tested. Experiment 3 was carried out in soil with excess of heavy metals and in three vine cultivation systems (vine in monoculture, vine in consortium with Paspalum notatum and vine in consortium with Paspalum plicatulum). The following experiments were evaluated: biomass production and growth rates, subcellular distribution of Mn, chlorophyll a fluorescence, leaf gas exchange with the environment, photosynthetic pigments, antioxidant enzyme activity, root system biometry, stomatal density and nutrient concentrations in plant tissues. Grasses showed Mn tolerance potential, with high concentrations in tissues, mainly in cell walls and vacuoles. However, Lolium multiflorum showed symptoms of toxicity to excess Mn, characterized by the presence of brown necrotic spots on old leaves, as well as some physiological variables were affected. Excess Cu is potentially more toxic than Mn, affecting several physiological responses in grasses, as well as inhibiting root growth and leaf chlorosis. In intercropping in soil contaminated with heavy metals, the grass species Paspalum notatum was more sensitive to excess elements, from the appearance of leaf chlorosis. However, the intercropping of vines with Paspalum notatum favored the photosynthesis responses of the vines and reduced the concentration of metals in the tissues. Therefore, the species of Paspalum notatum can be seen as an indicator plant of contaminated soils and the maintenance of native grasses between the vineyards is recommended, due to the phytostabilization and conservation potential of the native species of the Pampa biome, in southern Brazil.